A new Raspy Cricket from the northern Australian Rainforests (Orthoptera: Gryllacrididae) - Rentz, Dcf; Su, You Ning; Béthoux, Olivier (Zootaxa, 2018)
An Australian Raspy Cricket, Chauliogryllacris acaropenates Rentz, Su, Béthoux, sp. nov. is described. This cricket was found to harbor a number of mite species of interest to acarologists and the name was needed for them to proceed with their studies. A key to the males of the described species of Chauliogryllacris is provided along with numerous illustrations of the described cricket. Observations and comments on its biology, behavior and ecology are presented.